THE INFLUENCE OF WORK ENVIRONMENT AND ORGANIZATIONAL CULTURE ON EMPLOYEES' JOB SATISFACTION AT PT BUSANA REMAJA AGRACIPTA YOGYAKARTA - Latifatun, Latifatun; Chasanah, Uswatun; Zuraida, Lukia (Prosiding Seminar Nasional dan Call Paper STIE Widya Wiwaha, 2023)
Abstract This research is based on the problem of a work environment that is not conducive due to hot air temperatures and an unfavorable working atmosphere and there are unfavorable attitudes and ethics of some employees which affect the level of employee job satisfaction. The purpose of this research is to explain the effect of work environment and organizational culture on employee job satisfaction and to show the most influential variables on employee job satisfaction at PT Busana Remaja Agracipta Yogyakata. In this study the sample was calculated using the Slovin formula. The sample in this study were employees of PT Busana Remaja Agracipta Yogyakarta with a total of 50 respondents. The analytical method uses multiple linear regression analysis with the help of the SPSS version 22 program. This research uses quantitative methods. The results showed that the work environment has an effect on employee job satisfaction, organizational culture has no effect on employee job satisfaction, and simultaneously work environment and organizational culture have an effect on employee job satisfaction at PT Busana Remaja Agracipta Yogyakarta. The results showed that the most dominant variable that influences job satisfaction is the work environment. Analysis of the coefficient of determination obtained is 0.461 which means the work environment and organizational culture have a significant effect on job satisfaction by 46.1 percent. While the remaining 53.9 percent is influenced by other variables not examined.